Ranking transparency guidelines in Platform-to-Business Regulation to prevent algorithmic discrimination of consumers - Argelich Comelles, Cristina (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This paper examines the ranking transparency guidelines of online platforms in the P2B Regulation, as a legal treatment of algorithmic discrimination in consumer contracts. Therefore, this work considers duties related to standard contract terms, as well as others related to the right to information, the processing of personal data, contractual good faith, and remedies for breach of contract.
Keywords: Online platforms; consumer protection; providers of online intermediation services; business users; ranking